Quantitative observations of cavitation activity in a viscoelastic medium. - Collin, JR; Coussios, C (2011)
Quantitative experimental observations of single-bubble cavitation in viscoelastic media that would enable validation of existing models are presently lacking. In the present work, single bubble cavitation is induced in an agar gel using a 1.15 MHz high intensity focused ultrasound transducer, and observed using a focused single-element passive cavitation detection (PCD) transducer. To enable quantitative observations, a full receive calibration is carried out of a spherically focused PCD system by a bistatic scattering substitution technique that uses an embedded spherical scatterer and a hydrophone. Adjusting the simulated pressure received by the PCD by the transfer function on receive and the frequency-dependent attenuation of agar gel enables direct comparison of the measured acoustic emissions with those predicted by numerical modeling of single-bubble cavitation using a modified Keller-Miksis approach that accounts for viscoelasticity of the surrounding medium. At an incident peak rarefactional pressure near the cavitation threshold, period multiplying is observed in both experiment and numerical model. By comparing the two sets of results, an estimate of the equilibrium bubble radius in the experimental observations can be made, with potential for extension to material parameter estimation. Use of these estimates yields good agreement between model and experiment.